THE READINESS FOR INTERPROFESSIONAL EDUCATION IMPLEMENTATION DURING COVID-19 PANDEMIC IN INDONESIA: A DESCRIPTIVE STUDY - Sarah Firdausa; Rachmah Rachmah; Azizah Vonna; Teuku Renaldi; Noraliyatun Jannah; Masra Lena Siregar; Sri Wahyuni; Dedy Syahrizal (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: The importance of the interprofessional education (IPE) program has been depicted through various forms of the IPE curriculum. The COVID-19 pandemic has forced a change in the implementation of IPE; this has caused the method of implementing IPE to change online. This study aims to assess the readiness of three different healthcare professions for implementing IPE using the Readiness for Interprofessional Learning Scale (RIPLS).Methods: The RIPLS survey was completed by 108 medical students, 40 pharmacy students, and 30 nursing students at Universitas Syiah Kuala, Indonesia. The survey was done after the students carried out the online IPE intervention, which was held during the COVID-19 pandemic. They also completed open-ended questions reflecting their attitude towards and experience from the online IPE implementation.Results: There was no significant difference regarding student readiness for interprofessional learning among the three academic disciplines. Generally, as many as 57.9% of students showed a positive perception of IPE. Separate analysis for each study program showed that all of them were in the high range of scores for positive perception. Pharmacy students have the highest positive perception of IPE (60%), while medical and nursing students’ scores were 54.6% and 53.3%, respectively. Qualitative interviews revealed that: 1) the scheduling of IPE implementation was not suitable for the students, 2) the online communication between professions was not as effective as expected challenging, and 3) there was a growing awareness to respect other professions.Conclusion: It can be concluded that conducting the IPE program during the COVID-19 pandemic experienced many obstacles, especially communication. However, it still maintains the main objective of IPE, which is to respect other professions.